Proceedings of the fifteenth annual conference of the Research and Statistices Offices held at Zaranda Hotels, Bauchi State fromm October 16th - 20th, 2006 : inflation targeting in Nigeria - Central Bank of Nigeria, Research and Statistics Department; Mordi, C.N.O. (Abuja, Nigeria : Central Bank of Nigeria, 2006)
This book is a compilation of the papers presented at the 15th annual Conference of the Research Department held in Bauchi in 2006.
Includes bibliographical references
ijb, 24/10/2018
Loans
Keywords: Inflation